Serum secreted phosphoprotein 1 level is associated with plaque vulnerability in patients with coronary artery disease - Huang, Ke; Chen, Shuai; Yu, Lin-Jun; Wu, Zhi-Ming; Chen, Qiu-Jing; Wang, Xiao-Qun; Li, Fei-Fei; Liu, Jing-Meng; Wang, Yi-Xuan; Mao, Lin-Shuang; Shen, Wei-Feng; Zhang, Rui-Yan; et al. (Frontiers in Immunology, 2024)
Background: Vulnerable plaque was associated with recurrent cardiovascular events. This study was designed to explore predictive biomarkers of vulnerable plaque in patients with coronary artery disease.To reveal the phenotype-associated cell type in the development of vulnerable plaque and to identify hub gene for pathological process, we combined single-cell RNA and bulk RNA sequencing datasets of human atherosclerotic plaques using Single-Cell Identification of Subpopulations with Bulk Sample Phenotype Correlation (Scissor) and Weighted gene co-expression network analysis (WGCNA). We also validated our results in an independent cohort of patients by using intravascular ultrasound during coronary angiography.Results: Macrophages were found to be strongly correlated with plaque vulnerability while vascular smooth muscle cell (VSMC), fibrochondrocyte (FC) and intermediate cell state (ICS) clusters were negatively associated with unstable plaque. Weighted gene co-expression network analysis showed that Secreted Phosphoprotein 1 (SPP1) in the turquoise module was highly correlated with both the gene module and the clinical traits. In a total of 593 patients, serum levels of SPP1 were significantly higher in patients with vulnerable plaques than those with stable plaque (113.21 [73.65 -47.70] ng/ml versus 71. 08 [20.64 -135.68] ng/ml; P < 0.001). Adjusted multivariate regression analysis revealed that serum SPP1 was an independent determinant of the presence of vulnerable plaque. Receiver operating characteristic curve analysis indicated that the area under the curve was 0.737 (95% CI 0.697 -0.773; P < 0.001) for adding serum SPP1 in predicting of vulnerable plaques.Elevated serum SPP1 levels confer an increased risk for plaque vulnerability in patients with coronary artery disease.